Factors Influencing Social Participation Among Persons With Neuromyelitis Optica Spectrum Disorders: A Cross-Sectional Study - Jia, Mengmeng; Fan, Ping; Ning, Lin; Ruan, Hengfang; Wang, Tong; Qiu, Wei; Li, Huijuan; Li, Kun (Frontiers in Neurology, 2022)
Background Neuromyelitis optica spectrum disorders seriously hinder social participation. Only clarifying the status of social participation and the factors most strongly influencing it can promote better-targeted support for those with neuromyelitis optica spectrum disorders. Objectives To explore the factors influencing social participation among persons with neuromyelitis optica spectrum disorders. Methods 138 persons with neuromyelitis optica were recruited by convenience sampling. They completed the Impact on Participation and Autonomy Questionnaire, and were rated using the Barthel index, the Beck Anxiety Inventory and the Beck Depression Inventory. The data were used to evaluate a generalized linear model predicting social participation. Results The respondents mostly perceived good or very good possibilities of social participation, but participation outdoors and in social relations were considered more restricted. Ability in the activities of daily living, education level, bladder and bowel dysfunction, and depression were four significant predictors of social participation. Conclusions Strengthening training in the activities of daily living, continuing education, giving positive psychological support and helping with bladder and bowel problems may help to promote social participation among those with neuromyelitis optica spectrum disorders.